(untitled) (Eurasian Journal of Philology Science and Education, 2016)
The article describes actual problems ofteaching of practical Russian language course in phonetic aspect. Special attention is paid to studying the correct pronunciation of sounds, syllables, words, their discernment in speech, developmentand automation of audio-articulatory skills, education, phonetic hearing students. In the article the questions of development and automation of pronunciation skills, the education of the phonetic hearing students. In the article the questions of development and automation of pronunciation skills learning sounds in learning speech and action game, orthoepicnorms assumes observance of pronunciation skills, the study of the phonetic unity of word, created and syllabic rhythm